Preparation and Photocatalytic Activities of Nano-Porous ZnO Thin Film - Wang, Peng; Li, Changquan; Wang, Fajun; Ou, Junfei; Xue, Mingshan (Asian Journal of Chemistry, 2015)
A nano-porous ZnO film was prepared by using the porous anodic alumina template method. X-ray diffraction analysis and scanning electron microscopy were used to characterize the nano film. The photocatalytic properties of nano-porous ZnO films were investigated. The results show that the immersion time has great impact on the formation of the nano-porous ZnO film. The holes of porous anodic alumina template was gradually covered with ZnO nanomaterial and became smaller with increasing the immersion time. Finally, it was completely covered with ZnO. When exposed under UV radiation, the degradation rate of methyl orange increases with the increase of the amount of nano-porous ZnO film catalyst and with the exposure time. However, it decreases with increasing of the concentration of methyl orange.